Influencing the froth flotation of LiAlO2 and melilite solid solution with ionic liquids. Issue 45 (17th October 2022) - Qiu, Hao; Degenhardt, Christin; Feuge, Niklas; Goldmann, Daniel; Wilhelm, René
Abstract : The hardness of anions in ionic liquids used in a froth flotation have a significant influence on the process. Abstract : In the present work experiments for single mineral flotation against LiAlO2 and melilite s.s. were carried out for seven ionic liquids (ILs). From these, IL-1 with an imidazolium cation and a bromide anion and IL-7 with a pyridinium cation and a bromide anion were selected for further flotation experiments (dosage, pH). Flotation experiments were also conducted using naphthenic acid, a conventional flotation fatty acid-based collector, and FS-2, a commercial collector in order to compare the results with ILs. Moreover, the effects of different anions in the ILs on the flotation were evaluated and a significant influence on the hardness of anions was found on the flotation process. Finally, a pre-functionalization was also explored with modified cholesterol derivatives, comparing the effect of cholesterylsulfate and cholesterylphosphate on the flotation of LiAlO2 and melilite s.s. This study is vital for the further optimization of lithium recovery from the pyrometallurgical recycling path of lithium-ion batteries and the flotation of primary minerals such as aluminosilicates.